The Apostle of Struggle: Reappraising Howard Thurman on Paul - Eisenstadt, Peter R. (Church history, 2024)
Howard Thurman, the great 20th-century African American thinker and pastor, has often been characterized as holding an antagonistic view of the Apostle Paul, based primarily on several passages in his most important work, Jesus and the Disinherited (1949). One of those passages describes the anti-Pauline position of his grandmother, a former slave, Nancy Ambrose. In this article we argue that Thurman was, in contrast to his grandmother, oftentimes an admirer of Paul. Our thorough consideration of Thurman's published and unpublished work, as well as the work of his various intellectual and religious mentors, uncovers that he had a much more nuanced position on Paul than is normally described. He saw Paul as a profoundly radical and original thinker, who was nonetheless compromised by his Roman citizenship, distancing himself from his fellow Jews. For Thurman, a mentor to many in the civil rights movement, the question of citizenship was crucial, and he used Paul to help explore the complex intellectual, religious, and social situations of African Americans, caught between two worlds, ambivalent about trying to fit into a world that was ambivalent about them. In this way, for Thurman, Paul was a model of personal struggle and religious complexity.